Cognitive development in very vs. moderately to late preterm and full-term children: Can effortful control account for group differences in toddlerhood? - Voigt, Babett; Pietz, Joachim; Pauen, Sabina; Kliegel, Matthias; Reuner, Gitta (Early human development, 2012)
Preterm birth is thought to have an adverse impact on cognitive development and self-regulation. Examining the effect of very vs. moderately to late premature birth on cognitive development and effortful control, as well as evaluating whether effortful control explains the link between preterm birth and poorer cognitive development. Fifty-eight very preterm children (<32weeks gestation or <1500g birth weight), 88 moderately to late preterm children (≥32weeks gestation and ≥1500 birth weight) and 86 full-term children (≥38weeks gestation and ≥2500g birth weight) were examined at the corrected age of 24months. Observational and parent-report measures of effortful control as well as the Bayley Scales of Infant Development II (BSID II, Mental Scale) as a measurement of cognitive development were analyzed. Very preterm and moderately to late preterm children showed significantly lower cognitive performance compared to full-term children. Lower effortful control scores (on observational measures, but not on parent-reports) were merely found for very preterm children compared to full-term children. Observational measures of effortful control partially mediated the effects of very preterm birth on cognitive performance, but did not explain the effects of moderately to late preterm birth on cognitive performance. Preterm birth in general is related to poorer cognitive performance in toddlerhood. In addition, effortful control mediates the effects of very preterm birth on cognitive development. Findings suggest that different mechanisms link moderately to late premature birth to poor cognitive development.